Comparative characteristic of high-quality bentonite deposits of Russia and some foreign countries - P E Belousov (RUDN Journal of Engineering Research, 2013)
There is a brief geological structure of Tihmenevo, Dash-Salahly and Greek group of deposits. Their mineral and chemical structures, and comparative characteristic are given. The main directions of use of bentonites of these deposits are described.